Struktur dan Kemampuan Tumbuh Kembali Hutan Mangrove Cikiperan Cilacap - Edy Yani (Fakultas Biologi | Universitas Jenderal Soedirman, 2006)
Study was conducted to know forest structure and regeneration of mangrove Cikiperan Cilacap. Transect method was used for this study, the data of seedling were collected by quadrat method, sapling and tree were collected by quarter method. The result of this research showed there were 7 species seedling, 11 species sapling and 18 species trees. Dominant species was Rhizophora mucronata, Rhizophora apiculata, Bruguiera gymnorhiza, Avicenia alba, Aegiceros corniculatum, Nypa fruticans, and Ficus retusa. The forest of mangrove regeneration was generally very good. Seven species, however, were recorded in critical condition, i.e. Ceriops tagal, Sonneratia alba, Intsia bijuga, Cynometra ramniflora, Cerbera adolam, Leucaena leucodendrom, and Lumnitzera littorea.